2015
DOI: 10.1007/s10120-015-0500-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the diagnostic efficacy of white light endoscopy and magnifying endoscopy with narrow band imaging for early gastric cancer: a meta-analysis

Abstract: Objective Magnifying endoscopy with narrow band imaging (ME-NBI) is widely used in gastroscopy, especially in the diagnosis of early gastric cancer. The purpose of this meta-analysis is to compare the diagnostic efficacy of white light imaging (WLI) and that of ME-NBI for early gastric cancer. Methods PubMed/MEDLINE, EMBASE, and the Cochrane Library were searched to identify studies which met the inclusion criteria. A random-effects model was used to calculate overall sensitivity, specificity, and the area und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(51 citation statements)
references
References 32 publications
1
48
0
2
Order By: Relevance
“…By now, many new advanced approaches providing better visualization of gastric mucosa lesions have been developed, such as chromoendoscopy [62], confocal laser endomicroscopy [63], narrow-band imaging endoscopy [64], magnifying endoscopy [65] and narrow-band imaging with magnifying endoscopy [66]. A large number of studies showed that these new advanced endoscopic imaging technologies have better accuracy for diagnosing premalignant gastric lesions than standard ‘white light' endoscopy [67,68,69]. …”
Section: Prevention Strategies For Gastric Cancermentioning
confidence: 99%
“…By now, many new advanced approaches providing better visualization of gastric mucosa lesions have been developed, such as chromoendoscopy [62], confocal laser endomicroscopy [63], narrow-band imaging endoscopy [64], magnifying endoscopy [65] and narrow-band imaging with magnifying endoscopy [66]. A large number of studies showed that these new advanced endoscopic imaging technologies have better accuracy for diagnosing premalignant gastric lesions than standard ‘white light' endoscopy [67,68,69]. …”
Section: Prevention Strategies For Gastric Cancermentioning
confidence: 99%
“…The use of NBI also improves the diagnosis of early gastric cancer [48-51] and is also helpful in the preoperative demarcation of cancer to prevent positive surgical margins postoperatively [48, 51, 52]. NBI should be seen as a complement to WL, improving the diagnosis and detection of extensive intestinal metaplasia and superficial lesions with dysplasia and cancer [46].…”
Section: Stomachmentioning
confidence: 99%
“…High resolution NBI endoscopy is useful for predicting H. pylori infection and the histological severity of gastritis and is valuable for predicting gastric atrophy in the entire stomach (Tahara et al, 2009). Furthermore, high resolution endoscopy with narrow band imaging has good efficacy for detecting early gastric cancer (Hang et al, 2015;Zhang et al, 2015). The Kyoto global consensus report on H. pylori gastritis suggested that atrophic mucosa and intestinal metaplasia can be accurately detected by imageenhanced endoscopy, after appropriate training (Kentaro Sugano et al, 2015).…”
Section: Introductionmentioning
confidence: 99%